Uterine artery embolization for the treatment of symptomatic myomas in Brazilian women - Sena-Martins, Maurício; Roteli-Martins, Cecilia Maria; Tadini, Valdir; Souza, Gustavo Antonio de; Kisilevzky, Nestor; Lazar Junior, Felipe (São Paulo Medical Journal, 2003)
CONTEXT: Uterine myomas are benign tumors that mostly occur in women of reproductive age at a frequency ranging from 20 to 25%. The symptoms are increased menstrual flow, pain and compressive signs. New treatments have been proposed and uterine artery embolization is one of them. OBJECTIVE: To evaluate the effects of treatment by embolization of the uterine artery, in women with symptomatic myomas. Uterine and dominant myoma volumes and the major symptoms were evaluated before treatment and 12 weeks later. TYPE OF STUDY: Open clinical trial. SETTING: A tertiary-care women’s hospital. PARTICIPANTS: The study was conducted on 32 women with symptomatic single or multiple myomas of the uterine body, seen at the outpatient unit from May 2000 to September 2001. MAIN MEASUREMENTS: The patients were submitted to gynecological examination and abdominal and endovaginal pelvic ultrasonography, and the examinations were repeated 12 weeks after the first procedure. Uterine artery embolization using PVA (polyvinyl alcohol) particles of 355-700 µ was performed by catheterization of the right femoral artery in 30 women and by bilateral catheterization in two. RESULTS: Before embolization, the mean uterine volume of the 32 women was 455 cm3 and the mean volume of the dominant myoma was 150 cm3. Twelve weeks after embolization, the mean uterine volume was 256 cm3 and the mean volume of the dominant myoma was 91 cm3, with p < 0.01 in both cases. Twelve weeks after the treatment, all the women answered a questionnaire, which showed that 71% had improvement in menstrual regularity, 90% decreased menstrual volume and 81% shortened menstrual duration. The most frequent immediate post-procedure symptoms, established as complications, were pain (100%) and fatigue (34%). One woman had myoma degeneration and was submitted to myomectomy. CONCLUSION: The significant reduction in uterine and dominant myoma volume confirms the validity of the treatment of symptomatic myomas by the technique of uterine artery embolization in Brazilian women. There was significant reduction in menstrual flow and duration, as well as better cycle regularity in the women studied. The few adverse effects observed in the sample studied mainly involved pain immediately after embolization.